Determining the clinical significance of the PROMIS physical function score in the setting of femur fractures. - Myhre, Luke; Olsen, Zachary; Li, Haojia; Zhang, Yue; Cizik, Amy M.; Haller, Justin (European Journal of Orthopaedic Surgery & Traumatology, 2023)
Background: To adequately utilize patient reported outcome scores in the clinical setting, accurate determination of a cohort-specific minimal clinically important differences (MCID) is necessary. The purpose of this study was to assess MCID for Patient Reported Outcome Information System Physical Function Scores (PROMIS®) Physical Function (PF) in a sample of patients who have undergone operative fixation for femur fractures. Methods: All patients at a single Level 1 trauma center who were treated for operative femur fractures were identified by Current Procedural Terminology (CPT) codes (27,244, 27,245, 27,506, 27,507). PROMIS PF was collected as part of routine clinical care via computer adaptive testing (CAT). MCID calculations were performed using both anchor-based and distribution-based methods. Results: A total of 182 patients with 723 score observations were included in the overall distribution-based analysis and 131 patients with 309 score observations were included in the anchor-based analysis. In the overall cohort, the average age was 53.1 (SD 22.3), and 45% of participants were female. MCID for PROMIS PF scores was 5.43 in the distribution-based method and 5.18 in the anchor-based method. Overall scores in the distribution group improved from mean of 27.4 (SD 7.0) at the first postoperative visit to a mean of 36.7 (SD 10.0) at a subsequent follow up visit. Overall scores in the anchor group improved from mean of 26.7 (SD 7.3) at the first postoperative visit to a mean of 37.5 (SD 9.3) at a subsequent follow up visit. Conclusions: This study identifies two MCID values (5.18, 5.43) based on two calculation methods for PROMIS physical function scores in the operative femur fracture population. This data could be helpful in targeting postoperative patients who fall below expected norms or in allowing clinical correlation with changes in surgical practice.